LncRNA MEG3 promotes neuronal apoptosis in rats with ischemic cerebral infarction via the TGF-β1 pathway: LncRNA MEG3 promotes neuronal apoptosis - Long, Shiyu; Chen, Jingli; Tan, Shuwei; Zhou, Rong; He, Su; Jia, Jiedeng (Cellular and Molecular Biology, 2023)
To study the influence of long non-coding ribonucleic acid maternally expressed gene 3 (lncRNA MEG3) on the neuronal apoptosis in rats with ischemic cerebral infarction, and to analyze its regulatory effect on the transforming growth factor-beta 1 (TGF-β1) pathway. A total of 36 Sprague-Dawley rats were randomly assigned into sham group, model group and low expression group. Ischemic cerebral infarction modeling was constructed in rats of the model group and low expression group. Corresponding adenoviruses were intracranially injected in rats of low expression group to knock down lncRNA MEG3 expression. At 24 h after the operation, the neurological function of rats was evaluated in each group, and the expression level of lncRNA MEG3 in cerebral tissues was determined using quantitative polymerase chain reaction (qPCR). The infarct size was measured via 2,3,5-triphenyltetrazolium chloride (TTC) staining. The apoptosis level of neurons in cerebral tissues was determined using terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) staining. Besides, enzyme-linked immunosorbent assay (ELISA) was performed to determine the contents of inflammatory factors in cerebral tissues. Expression levels of apoptosis-associated proteins and vital genes in the TGF-β1 signaling pathway in rat cerebral tissues were measured using Western blotting. Compared with the sham group, rats in the model group exhibited substantial increases in the neurological score and apoptosis level of neurons (p<0.01). Relative levels of lncRNA MEG3, interleukin (IL)-6, tumor necrosis factor-alpha (TNF-α), Caspase-3, TGF-β1, small mothers against decapentaplegic homolog 2 (Smad2) and Smad3 (p<0.01) were higher in a model group than those in sham group. Notable declines in the content of IL-10 (p<0.01) and the ratio of B-cell lymphoma 2 (Bcl-2)/Bcl associated X protein (Bax) (p<0.01) were seen in the model group compared with the sham group. The abovementioned changes in the model group were partially abolished in the low expression group. LncRNA MEG3 is upregulated in the cerebral tissues of rats with ischemic cerebral infarction. It induces an inflammatory response, expands cerebral infarct size, and promotes neuronal apoptosis and impairment by activating the TGF-β1 pathway.